(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
LGBTQIA+ individuals are more likely to face discrimination because they are often encouraged to conform to society’s conventional views of being male or female. In this study, the researchers aimed to explore the lived experiences of LGBTQIA+ employees regarding gender discrimination in the workplace, particularly in Novaliches, Quezon City. Most of the LGBTQIA+ employees encountered problems with gender discrimination, such as Gender Stereotyping and Gender Bias. They had different views and attitudes toward gender discrimination. Some of them react to it negatively, but most of them respond to gender discrimination positively. Gender discrimination also had different impacts on the participants. Most of them are influenced positively, some negatively, and others unbothered by gender discrimination. They also utilized different coping mechanisms to deal with those problems brought about by gender discrimination in the workplace. They were affected differently, both positively and negatively. However, despite that, they are still willing to advise their fellow LGBTQIA+ individuals who also experienced gender discrimination at their workplace. Lastly, the participants mentioned the desires they wish to attain in society as members of the LGBTQIA+ community who experienced gender discrimination in many forums. The results showed that most LGBTQIA+ employees encountered problems with gender discrimination. They had different views and attitudes toward gender discrimination. Gender discrimination also had different impacts on the participants. They also utilized different coping mechanisms to deal with those problems brought about by gender discrimination in the workplace. It is recommended that LGBTQIA+ employees should continue to strive and maintain a positive mindset despite being discriminated against because of their gender.Government/Employment Agencies should create or improve policies that benefit people, regardless of gender, to provide everyone with equal job opportunities.